2022
DOI: 10.1002/hpja.637
|View full text |Cite
|
Sign up to set email alerts
|

“Drugs and alcohol get talked about, why not betting?” Young men's qualitative insights about strategies to prevent gambling harm

Abstract: Issues addressed Research is needed to understand young people's perspectives about public health promotion strategies relevant for their health and wellbeing. This study provides suggestions from young male gamblers about sports betting harm prevention and reduction strategies. Methods In‐depth interviews were conducted with 16 young men aged 18 to 24 years, from Melbourne, Victoria, who regularly engaged in sports betting. A critical qualitative inquiry approach, using methods of constructivist grounded theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Finally, this study showed that in addition to reframing messages about gambling, people who have experienced gambling harm clearly support a range of strategies which are consistent with the public health approach to harm prevention. This aligns with previous evidence that gamblers also want governments to take legislative steps to restrict the gambling industry (Marko et al, 2022 ; McCarthy et al, 2022a ; Nyemcsok et al, 2022a ), as they have done alongside reframing messaging in other public health areas such as tobacco (Chapman and Freeman, 2008 ). In the Australian state of Victoria where many of the participants for this study resided, the Public Health and Wellbeing Act recognizes that governments have a “ a significant role in promoting and protecting the public health and wellbeing… [and] promoting conditions in which persons can be healthy” (Parliament of Victoria, 2008 :s4).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, this study showed that in addition to reframing messages about gambling, people who have experienced gambling harm clearly support a range of strategies which are consistent with the public health approach to harm prevention. This aligns with previous evidence that gamblers also want governments to take legislative steps to restrict the gambling industry (Marko et al, 2022 ; McCarthy et al, 2022a ; Nyemcsok et al, 2022a ), as they have done alongside reframing messaging in other public health areas such as tobacco (Chapman and Freeman, 2008 ). In the Australian state of Victoria where many of the participants for this study resided, the Public Health and Wellbeing Act recognizes that governments have a “ a significant role in promoting and protecting the public health and wellbeing… [and] promoting conditions in which persons can be healthy” (Parliament of Victoria, 2008 :s4).…”
Section: Discussionsupporting
confidence: 86%